2017
DOI: 10.1103/physrevlett.119.227801
|View full text |Cite
|
Sign up to set email alerts
|

Free Surface Relaxations of Star-Shaped Polymer Films

Abstract: The surface relaxation dynamics of supported star-shaped polymer thin films are shown to be slower than the bulk, persisting up to temperatures at least 50 degrees above the bulk glass transition temperature Tgbulk. This behavior, exhibited by star-shaped polystyrenes (SPSs) with functionality f = 8-arms and molecular weights per arm Marm < Me (Me is the entanglement molecular weight), is shown by molecular dynamics simulations to be associated with a preferential localization of these macromolecules at the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“…Based on our experimental investigations, we attribute the ~45% faster physical aging response of ultra‐high MWs ≥ 6500 kg mol −1 thin PS films, relative to equivalent films of (merely) high MWs ≤ 3500 kg mol −1 , to a diminished gradient in dynamics near the free surface of these films. These results contribute to the growing reports in the literature that chain connectivity and entropy are additional factors influencing interfacial effects and dynamical gradients in thin films beyond the well‐characterized enthalpic interactions.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Based on our experimental investigations, we attribute the ~45% faster physical aging response of ultra‐high MWs ≥ 6500 kg mol −1 thin PS films, relative to equivalent films of (merely) high MWs ≤ 3500 kg mol −1 , to a diminished gradient in dynamics near the free surface of these films. These results contribute to the growing reports in the literature that chain connectivity and entropy are additional factors influencing interfacial effects and dynamical gradients in thin films beyond the well‐characterized enthalpic interactions.…”
Section: Discussionsupporting
confidence: 67%
“…However, several recent studies have reported differences in confinement behavior associated with chain length, stiffness, entanglements, and chain architecture that are unexpected given the primarily enthalpic understanding developed over the years. This suggests that entropic effects may also play a modifying role in understanding confinement effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural dynamics, the molecular mechanism associated with the vitrification of liquids, is altered by the presence of interfaces [1,2]. Because of the smaller number of neighbors (lower density ρ), molecules at the free surface with air are expected to experience faster dynamics [3][4][5][6][7][8].…”
mentioning
confidence: 99%
“…In the case of free surfaces, that is, an interface with air, vacuum or inert gases, molecules move faster [11][12][13][14]. This enhancement in relaxation rate is probably due to the larger space available to molecules, as density decreases while approaching the free surface [15,16]. A more intriguing scenario is observed in proximity of hard walls, where the dynamics can both accelerate or slowdown, depending on the adsorbed amount [17].…”
Section: Introductionmentioning
confidence: 99%